2011
DOI: 10.2478/s11535-011-0089-6
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal insulin affects adenyl cyclase system in rat tissues in neonatal diabetes

Abstract: Intranasal insulin affects adenyl cyclase system in rat tissues in neonatal diabetes Abbreviations:AC -adenylyl cyclase; AC system -adenylyl cyclase signaling system; DM -diabetes mellitus; EMD-386088 -5 -c h l o r o -2 -m e t h y l -3 -( 1 , 2 , 3 , 6 -tetrahydro-4-pyridinyl)-1H-indole; GppNHp -b,g-imidoguanosine-5'-triphosphate; 5-HT receptor -5-hydroxytryptamine receptor; hCG -human chorionic gonadotropin; PACAP-38 -pituitary adenylyl cyclase-activating peptide-38. IntroductionHypertension, coronary heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 57 publications
3
27
0
2
Order By: Relevance
“…As demonstrated earlier by us, long-term treatment of rats with the prolonged model of mild DM1 or the neonatal model of DM2, using I-I at the daily doses of 0.45-0.48 IU/rat, led to a partial restoration of activity of the brain adenylyl cyclase signaling system sensitive to monoamines and peptide hormones [24]. In our opinion, there are reasons to regard I-I-induced restoration of functional activity of the integrative network of the brain neurotransmitter systems in diabetic animals as one of the key factors responsible for an increase in sensitivity of the pituitary to TRH, enhanced synthesis and secretion of TSH by thyrotrophs and the restoration of HPT axis function.…”
Section: Endocrine Researchsupporting
confidence: 60%
See 1 more Smart Citation
“…As demonstrated earlier by us, long-term treatment of rats with the prolonged model of mild DM1 or the neonatal model of DM2, using I-I at the daily doses of 0.45-0.48 IU/rat, led to a partial restoration of activity of the brain adenylyl cyclase signaling system sensitive to monoamines and peptide hormones [24]. In our opinion, there are reasons to regard I-I-induced restoration of functional activity of the integrative network of the brain neurotransmitter systems in diabetic animals as one of the key factors responsible for an increase in sensitivity of the pituitary to TRH, enhanced synthesis and secretion of TSH by thyrotrophs and the restoration of HPT axis function.…”
Section: Endocrine Researchsupporting
confidence: 60%
“…Intranasal delivery of insulin to rat's brain was performed as described earlier [24]. Crystalline insulin (Sigma, St. Louis, Mo, USA) at concentrations 15, 22.5, 30, and 75 IU/ml was dissolved in 0.1 M citrate buffer, pH 4.5, and delivered intranasally to diabetic and nondiabetic rats once a day.…”
Section: Intranasal Delivery Of Insulinmentioning
confidence: 99%
“…A signi�cant reduction of AC effect of PACAP-38 having an important role in protection of neuronal cells from damage and neurodegenerative changes [31] speaks in favor of abnormalities in PACAP-mediated neuroprotection in the case of long-term T1DM. It has been noticed that short-term T1DM and neonatal T2DM had no effect on the regulation of brain AC activity and G s protein binding by PACAP-38 [16,25]. We showed that the 135-day therapy with I-I prevents the decline of AC stimulation induced by PACAP-38 in the diabetic brain.…”
Section: Column 1: Group Namementioning
confidence: 68%
“…As we showed earlier, in the model of short-term T1DM and the neonatal model of type 2 diabetes mellitus (T2DM), although the stimulating effects of serotonin on AC activity and GTP binding of G s proteins in the diabetic brain were reduced, the corresponding effects of EMD-386088 and, as a result, 5-HT 6 R-mediated AC signaling did not change [16,25]. ere was a decrease in the number of 5-HT 6 R and a reduced AC response to selective 5-HT 6 R agonists in the brain of patients with prolonged Alzheimer's disease due to the neurodegenerative alterations in neuronal and glial cells [28].…”
Section: Column 1: Group Namementioning
confidence: 80%
See 1 more Smart Citation